2003
DOI: 10.1021/jf034682w
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Clerodane Diterpenes from Macaranga monandra (L) Muell. et Arg. (Euphorbiaceae)

Abstract: Hexane and ethyl acetate phases of the methanol extract of Macaranga monandra showed fungal growth inhibition of Colletotrichum acutatum, C. fragariae and C. gloeosporioides, Fusarium oxysporum, Botrytis cinerea, Phomopsis obscurans, and P. viticola. Bioassay-guided fractionation led to the isolation of two active clerodane-type diterpenes that were elucidated by spectroscopic methods (1D-, 2D-NMR, and MS) as kolavenic acid and 2-oxo-kolavenic acid. A 96-well microbioassay revealed that kolavenic acid and 2-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
4
34
0
4
Order By: Relevance
“…The NMR spectra of 1 corresponded closely with those of vedelianin (6) 22 and schweinfurthin B (12). 20 In particular, the observation of a "quartet" with J = 3.5 Hz for H-3 was in complete agreement with the "quartet" observed for H-3 of schweinfurthin B with J = 3.…”
Section: Resultssupporting
confidence: 65%
“…The NMR spectra of 1 corresponded closely with those of vedelianin (6) 22 and schweinfurthin B (12). 20 In particular, the observation of a "quartet" with J = 3.5 Hz for H-3 was in complete agreement with the "quartet" observed for H-3 of schweinfurthin B with J = 3.…”
Section: Resultssupporting
confidence: 65%
“…Investigation of the Cameroonian plant, M. monandra for possible antifungal compounds was undertaken by Salah et al (2003). Bioassay-guided fractionation of the hexane and ethyl acetate fractions of the methanol extract led to the isolation of two active clerodane-type diterpenes (146 and 147).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Bioassay-guided fractionation of the hexane and ethyl acetate fractions of the methanol extract led to the isolation of two active clerodane-type diterpenes (146 and 147). A 96-well microbioassay revealed that kolavenic acid (146) and 2-oxo-kolavenic acid (147) produced moderate growth inhibition in Phomopsis viticola and Botrytis cinerea (Salah et al, 2003). Compound 146 was slightly more active against P. viticola and showed 50% growth inhibition at 30 µM, whereas 147 showed 46% growth inhibition.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 2 more Smart Citations